ISLAMIC LAW IN THE CONSTITUTION OF INDONESIA (a Study of Characteristics Sharia Local Regulations) - Mohamad Hidayat Muhtar; Nur Mohamad Kasim; Irma Suryani (TSAQAFAH, 2023)
Indonesia’s constitutional law embodies the ideals of Islamic law, guaranteeing the right to religion and worship in Article 29 of the 1945 Constitution. Local Sharia regulations, known as Sharia Perda, are one manifestation of this ideal. However, Sharia Perda is not without problems, such as discrimination and exclusivity towards non-Muslims and limitations on women’s freedom. This research aims to identify the main characteristics of Sharia Perda and discuss its compatibility with constitutional law. The research employs a normative juridical approach, analyzing relevant laws and regulations, and using the legal hermeneutic method to interpret their meaning and philosophy. Sharia Perda has two main characteristics: Sharia compliance and local speciƶcity. However, its implementation has resulted in controversies and conǁicts, such as the prohibition of alcohol and criminalization of pre-marital sex. These controversies arise from the tension between Islamic law principles and constitutional law, particularly regarding individual rights and freedoms. This study contributes to the discussion of the compatibility of Islamic law and constitutional law, highlighting the need to address the problems of Sharia Perda, particularly the limitations on women’s freedom and discrimination towards non-Muslims.